Diagnosing Qur'anic Reading Difficulties and Adaptive Islamic Education Strategies in an Indonesian Public Senior High School - Aisya Rismatul Saputri; Sururudin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study analyzes factors contributing to Qur'anic reading difficulties among eleventh-grade students at Indonesian public senior high school (Sekolah Menengah Atas/SMA), specifically State Senior High School 1 in Sarolangun Regency, and describes Islamic Religious Education (Pendidikan Agama Islam/PAI) teacher responses. Using a descriptive qualitative design, data were collected through classroom observation, in-depth interviews, and documentation. The findings indicate that students' difficulties are concentrated in Arabic articulation points (makharijul huruf), especially pharyngeal and emphatic letters, and in tajwid rules, particularly vowel-length regulation (mad), nasalization (ghunnah), and fluent pausing (waqaf). These technical difficulties interact with psychological barriers such as nervousness when reading aloud. The determinants include low intrinsic motivation, weak foundational religious learning, limited parental guidance, intensive gadget use that reduces murajaah or repetition time, and insufficient PAI lesson hours for individualized correction. Teachers responded through diagnostic screening, differentiated private tutoring, visual media-assisted quantum learning principles, routine recitation habits, theological encouragement, and progress-based academic reinforcement. The study argues that Qur'anic literacy support in public secondary schools requires an integrated humanistic-clinical pedagogy that combines technical remediation, affective support, and school-family collaboration.